Safety, tolerability, and seizure control during long‐term treatment with adjunctive brivaracetam for partial‐onset seizures. (6th June 2016) - Toledo, Manuel; Whitesides, John; Schiemann, Jimmy; Johnson, Martin E.; Eckhardt, Klaus; McDonough, Belinda; Borghs, Simon; Kwan, Patrick
Summary: Objectives: To report pooled safety/tolerability and seizure outcome data from adults with uncontrolled partial‐onset (focal) seizures (POS) receiving adjunctive brivaracetam (BRV) during phase IIb/III and long‐term follow‐up (LTFU) studies. Methods: Seizure outcome data were pooled from phase IIb (NCT00175929 and NCT00175825), III/IIIb (NCT00490035, NCT00464269, NCT00504881, and NCT01261325) and associated LTFU studies (NCT00175916, NCT00150800, and NCT01339559). Safety/tolerability data were pooled from these studies plus NCT01405508, NCT01653262, and NCT01728077 (LTFU). Patients received placebo (during core studies) or BRV 5–200 mg/day. Safety/tolerability and seizure outcomes (BRV modal doses 50–200 mg/day) were assessed until January 17, 2014. Results: Of 2, 186 patients (97.3% with POS and 2.7% with other seizure types) who received BRV 50–200 mg/day, 2, 051 (93.8%) completed core studies and continued in LTFU studies. Total BRV exposure: 5, 339.4 patient‐years (≥8.0 years in 41 patients); 6‐, 12‐, 24‐, and 60‐month retention: 91.0%, 79.8%, 68.1%, and 54.4%, respectively. Safety/tolerability data pooled from 2, 186 patients: ≥1 treatment‐emergent adverse event (TEAE) reported by 1, 848 (84.5%) patients; 1, 184 (54.2%) reported ≥1 TEAE considered treatment‐related. Most frequent TEAEs (≥10%): headache (20.9%), dizziness (17.5%), somnolence (15.2%), nasopharyngitis (13.2%), fatigue (11.3%), and convulsion (10.6%). Serious TEAEs (SAEs) and treatment‐related SAEs: 401 (18.3%) and 95 (4.3%) patients, respectively. Of 28 (1.3%) deaths, four (14.3%) were considered possibly treatment related by the investigator. Pooled seizure outcome data (1, 836 patients): median POS frequency/28 days at baseline was 8.9; on treatment, median percentage reduction from baseline in POS/28 days was 48.8%, and ≥50% responder rate was 48.7%. Complete seizure freedom: 4.9%, 4.2%, 3.0%, and 3.3% for ≥6, 12, 24, and 60 months, respectively. Improvements were seen in health‐related quality of life (HRQoL) from baseline, assessed by Quality of Life in Epilepsy Inventory‐31. Significance: Adjunctive BRV treatment in adults with POS was effective and generally well tolerated when administered long‐term (≥8.0 years). Retention was high and HRQoL improvements were observed.